2007
DOI: 10.1016/j.chemosphere.2007.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of leachate from pyrolysis residue of sewage sludge

Abstract: The pyrolysis residue (SP) of sewage sludge (SS) produced at 500 °C was subjected to batch and column leaching tests to investigate the release of its organic and inorganic constituents and metals. For comparison, incineration ash (SI) obtained from a SS incinerator was also tested. Pyrolysis and incineration reduced organic matter of SS from 0.78 kg kg -1 -dry SS to 0.16 and 0.01 kg kg -1 -dry SS, respectively. Heavy metals remained in SP without being volatilized, although Cd and Pb were transferred into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 15 publications
3
51
0
6
Order By: Relevance
“…However, it was previously demonstrated that Zn mobility/leachability (Bernardo et al, 2010) is suppressed in the extracted pyrolysis chars. Also, previous studies (Hwang et al, 2007;Kistler et al, 1987) have shown that pyrolysis may have a positive effect on the immobilization of heavy metals in solid chars. Table 3.…”
Section: Mineral Composition Of the Charsmentioning
confidence: 92%
“…However, it was previously demonstrated that Zn mobility/leachability (Bernardo et al, 2010) is suppressed in the extracted pyrolysis chars. Also, previous studies (Hwang et al, 2007;Kistler et al, 1987) have shown that pyrolysis may have a positive effect on the immobilization of heavy metals in solid chars. Table 3.…”
Section: Mineral Composition Of the Charsmentioning
confidence: 92%
“…4, that, comparing with raw sewage sludge and the sewage sludge residue after subcritical treatment, the content of element C in sewage sludge residue after supercritical treatment decreases obviously, showing that the decomposition of organic matters in sewage sludge residue is more thorough. Meanwhile, Fe, Al and Ca in sewage sludge residue after supercritical treatment can generate phosphate, aluminum phosphate and calcium phosphate with phosphorus, thus realizing the role of stabilizing the heavy metal ions [8,9] .…”
Section: Experiments Resultsmentioning
confidence: 99%
“…He et al [24] determined the chemical composition and thermal stability of solid residues, as well as migration and transformation of HMs during SS pyrolysis. Hwang et al [25][26] found that most HMs was completely retained by solid residue after SS pyrolysis treatment and the composition of raw SS had a significant influence on the quality of the resulting residue and thus, the mobility of HMs. Lu et al [27] also studied the influence of pyrolysis temperature on physical and chemical properties of pyrolysis residue.…”
Section: Introductionmentioning
confidence: 99%